Pengembangan Sistem Informasi Produk Finished Goods Menggunakan Appsheet pada PT. Miko Bahtera Nusantara - Muhammad Farhan Hilmi; Rukmana, Otong; Febri Suahati, Ajrina (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. PT Miko Bahtera Nusantara is a company engaged in the biotech industry with its flagship products, namely Biobo and Mylea. Both products are renewable environmentally friendly materials made from mushrooms (mycelium). The calculation of the Cost of Goods Manufactured (COGM) often experiences swelling and shrinkage because the current information system is not optimal, so recording errors usually occur. Based on this phenomenon, the problems in this study are formulated as follows: (1) How is the current information system running? (2) What are the storage information system requirements needed in the Pilot Production Department? (3) How is the development of the information system needed? (4) How is the trial of the new information system created? The method used in this study is the FAST (Framework for Application of Systems Thinking) method with a model-driven strategy. The instruments used in system development include Business Process Model and Notation (BPMN), Use Case Diagram, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), Platform Appsheet, and Google Sheets Database. The results of this study are in the form of a Finished Goods product information system application that has been tested to make recording more optimal. Abstrak. PT Miko Bahtera Nusantara merupakan perusahaan yang bergerak di bidang industri biotech dengan produk unggulannya, yaitu Biobo dan Mylea. Kedua produk tersebut adalah material ramah lingkungan terbarukan yang terbuat dari jamur (mycelium). Perhitungan Cost of Goods Manufactured (COGM) sering kali mengalami pembengkakan dan penyusutan karena sistem informasi yang berjalan saat ini belum optimal, sehingga sering terjadi kesalahan pencatatan. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana sistem informasi yang sudah berjalan saat ini? (2) Bagaimana kebutuhan sistem informasi penyimpanan yang diperlukan di departemen Pilot Production? (3) Bagaimana pengembangan sistem informasi yang dibutuhkan? (4) Bagaimana uji coba sistem informasi baru yang dibuat? Metode yang digunakan dalam penelitian ini adalah metode FAST (Framework for Application of Systems Thinking) dengan strategi model-driven. Instrumen yang digunakan dalam pengembangan sistem di antaranya Business Process Model and Notation (BPMN), Use Case Diagram, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), Platform Appsheet, dan Database Google Sheets. Hasil penelitian ini berupa aplikasi sistem informasi produk Finished Goods yang sudah teruji membuat pencatatan lebih optimal.